KEJELASAN SASARAN ANGGARAN DAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI PENGARUH KOMPETENSI PEGAWAI PADA KINERJA PENYERAPAN ANGGARAN - Arthana, I Made; Mimba, Ni Putu Sri Harta; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
This study aims to prove empirically regarding budget goal clarity and organizational commitment as a moderating effect of employees’ competence on budget absorption performance of working unit at the payment scope of the State Treasury Services Office of Denpasar. Sampling method used was a simple random sampling with a sample of 289 people. This study used primary data by distributing questionnaires as a hypothetical test tool. Secondary data as a complementary data being used was a budget data and realization of working unit at the payments scope of the State Treasury Service office of Denpasar in the year of 2014. Analysis technique being used was Moderated Regression Analysis. Results of study showed that employees’ competency have positive effect on budget absorption performance. Budget goal clarity and organizational commitment strengthened the effect of employees’ competence on budget absorption performance.
Keywords: employee competence; budget goal clarity; organizational commitment; budget absorption performance